Effects of marine protected areas under different management regimes in a hot spot of biodiversity and cumulative impacts from SW Atlantic - Motta, Fabio S.; Moura, Rodrigo L.; Neves, Leonardo M.; Souza, Gabriel R.S. [UNESP]; Gibran, Fernando Z.; Francini, Carlo L.; Shintate, Gustavo I.; Rolim, Fernanda A.; Marconi, Marina; Giglio, Vinicius J.; Pereira-Filho, Guilherme H. (Elsevier, 2021)
Marine protected areas (MPAs) represent a useful tool for resource management, as well as to conserve and/or restore biological communities. The level of protection is key factor influencing the marine biodiversity, where a more enforced protection is expected to drive positive outcomes. In 2008, a large MPAs network (∼11,380 km 2) was established in one of off the most populated and industrialized areas in the world (i.e., São Paulo State coast, southeast Brazil). Given many goods and services provided by marine ecosystems, this MPA network represents the most challenging marine conservation initiative in Brazil. Harboring​ areas with different socio-ecological contexts and management regimes, this MPA network provides a unique opportunity to investigate the effects of cumulative impacts. We contrasted the biomass and size structure of reef fish in three subtropical islands under different levels of enforcement. We analyzed the influence of variables as island size, benthic cover, depth, topographic complexity, wave exposure, and protection level on the biomass of reef fish assemblages. Protection level was the main attribute responsible to explain the high biomass of fish target species and small territorial herbivores. In sites sheltered from the waves, the biomass of groupers was ∼1600% higher within enforced area than that from open-access area. Beyond the idea of positive effects of enforcement on reef fish biomass and size, we add evidences that even under multiple stressors, the area-based management is still a strong tool to marine conservation.
Keywords: Conservation; Effectiveness; Fishing effects; MPA network; Reef fishes; Underwater visual census